If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5 + -6x) + 7 = -42x + -1 (5 * 7 + -6x * 7) + 7 = -42x + -1 (35 + -42x) + 7 = -42x + -1 Reorder the terms: 35 + 7 + -42x = -42x + -1 Combine like terms: 35 + 7 = 42 42 + -42x = -42x + -1 Reorder the terms: 42 + -42x = -1 + -42x Add '42x' to each side of the equation. 42 + -42x + 42x = -1 + -42x + 42x Combine like terms: -42x + 42x = 0 42 + 0 = -1 + -42x + 42x 42 = -1 + -42x + 42x Combine like terms: -42x + 42x = 0 42 = -1 + 0 42 = -1 Solving 42 = -1 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6b^2+4b-2=0 | | (8-7i)/(2-6i) | | 11.57-3n=4.67 | | 200.00+0.25=410.00 | | 2=13+0.5x | | x^2-x+1=-7 | | x^2-x+1=1 | | 6/g=42/36 | | x^2-x+1=-1 | | a-b/x=c | | Y+7=3(x-4) | | 1.5+x=0 | | 2(3x+7)=48 | | 2(3x+7)=56 | | 22+8h=-354 | | 2(3x+7)=31 | | 3=9-3f | | 1234*x+4=9876 | | sin3t=1/2 | | -x-4=11 | | u/3--20=24 | | 12x-8=70 | | (-3)*(-3)*(-3)*(-3)+x=10x | | 109-9v=19 | | 15x^3+11x^2-14x=0 | | 13=117-8w | | 81+x=10x | | v/7-2=1 | | 22-2k=14 | | 5.4=-logx | | -6(2-3x)-3=-15+2x | | (-3)*(-3)*(-3)+x=10x |